Rancang Bangun Mesin Pencacah Limbah Kotoran Sapi - Arifin, Zainal; Prasetyo, Singgih Dwi; Triyono, Teguh; Harsito, Catur; Yuniastuti, Endang (Jurnal Rekayasa Mesin, 2020)
Cattle farms produce waste which consisted of cow excrement in the form of solid, liquid, gas or cattle feed residual. Utilization of cow manure waste into organic compost requires proper processing technology which includes the technology of solid manure pulverizing and the technology of mixing raw materials. This research focuses on designing a cattle dung waste pulverizer. The methods used are numerical calculations, simulations using the Fusion 360 software, and fabrication based on Design for Manufacture and Assembly (DFMA). The main parts of the design include pulverizer, engine frame, cover (input and output hoppers), diesel motor, transmission belt and pulley. The safety factor obtained for the frame section was 4,645, for the cover section was 11.3, and for the counter section was 2,009 with assumptions of uniform load distribution of 20000 N. The power required for the design was 6.6 HP. The cattle dung waste pulverizer was built and tested using a diesel motor with a maximum power of 13 HP. The cattle dung waste pulverizer's capacity was 1500 kg/hour.